Accelerated Hypofractionated Magnetic Resonance Guided Adaptive Radiation Therapy for Ultracentral Lung Tumors - Alonso La Rosa; Kathryn E. Mittauer; Nema Bassiri; Amy E. Rzepczynski; Michael D. Chuong; Sreenija Yarlagadda; Tugce Kutuk; Nicole C. McAllister; Matthew D. Hall; Alonso N. Gutierrez; Ranjini Tolakanahalli; Minesh P. Mehta; et al. (Tomography, 2024)
Radiotherapy for ultracentral lung tumors represents a treatment challenge, considering the high rates of high-grade treatment-related toxicities with stereotactic body radiation therapy (SBRT) or hypofractionated schedules. Accelerated hypofractionated magnetic resonance-guided adaptive radiation therapy (MRgART) emerged as a potential game-changer for tumors in these challenging locations, in close proximity to central organs at risk, such as the trachea, proximal bronchial tree, and esophagus. In this series, 13 consecutive patients, predominantly male (n = 9), with a median age of 71 (range (R): 46–85), underwent 195 MRgART fractions (all 60 Gy in 15 fractions) to metastatic (n = 12) or primary ultra-central lung tumors (n = 1). The median gross tumor volumes (GTVs) and planning target volumes (PTVs) were 20.72 cc (R: 0.54–121.65 cc) and 61.53 cc (R: 3.87–211.81 cc), respectively. The median beam-on time per fraction was 14 min. Adapted treatment plans were generated for all fractions, and indications included GTV/PTV undercoverage, OARs exceeding tolerance doses, or both indications in 46%, 18%, and 36% of fractions, respectively. Eight patients received concurrent systemic therapies, including immunotherapy (four), chemotherapy (two), and targeted therapy (two). The crude in-field loco-regional control rate was 92.3%. No CTCAE grade 3+ toxicities were observed. Our results offer promising insights, suggesting that MRgART has the potential to mitigate toxicities, enhance treatment precision, and improve overall patient care in the context of ultracentral lung tumors.